Karakteristik Penderita Tuberculosis Multidrug Resistant (TB MDR) di Sulawesi Tenggara Tahun 2014-2017 - Zida Maulina Aini; Nur Martina Rufia (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2019)
ABSTRACTBackground:MDR TB is one type of bacterial tuberculosis resistance to first-line anti-TB drugs, Isoniazid and Rifampicin. Data from the Provincial Health Office of Southeast Sulawesi cases of MDR TB increase every year that is in 2014 there are 7 patients with MDR TB, 2015 there are 8 patients with MDR TB, 2016 there are 23 patients with MDR TB, and in 2017 there are 28 patients with MDR TB. The purpose of this study is to explain the characteristics of patients with MDR TB in Southeast Sulawesi in 2014-2017. Research Purpose: This study is to explain the characteristics of patients with MDR TB in Southeast Sulawesi in 2014-2017.  Research Method: The location of this study was in the Provincial Health Office of Southeast Sulawesi and Bahteramas General Hospital of Southeast Sulawesi Province with study population included all patients diagnosed with MDR TB in Southeast Sulawesi Province 2014-2017. The research data is processed to know the number and percentage of each characteristic of MDR TB patients in Southeast Sulawesi 2014-2017. Research result: The conclusion of the result of the study is characteristic of MDR TB patient in Southeast Sulawesi 2014-2017 dominated by age 15-55 years old, male gender, entrepreneur job, case of drop out treatment, examination of chest X-ray in the form of infiltrate and cavity, sputum smear examination (+1), the type of Rifampicin resistance, and is still temporarily treated.Keyword: MDR TB, age, sex, occupation, medical history, investigation, type of resistance and treatment outcome.